using identity (x+a)(x+b)=x2+x(a+b)+ab.
1.(abc-4)(abc-2)
2.(4a2+7)(4a2+5)
Answers
1..(abc-4)(abc-2)
we have to solve this problem using
(x+a)(x+b)=x^2+x(a+b)+ab.
where x=abc,a=-4 and b=-2.
(abc-4)(abc-2)=(abc)^2+abc(-4-(+2))+(-4×-2)
=a^2×b^2×c^2+abc(-4-2)+(+8)
=a^2×b^2×c^2-6abc+8✓
2. (4a^2+7)(4a^2+5)
we have to solve this problem using
(x+a)(x+b)=x^2+x(a+b)+ab.
where x=4a^2,a=7 and b=5.
(4a^2)^2 + 4a^2(7+5) +(7×5)
16a^4 + 4a^2(12) + 35
16a^2 + 48a^2 + 35✓
Life isn’t about waiting for the storm to pass… It’s about learning to dance in the rain.
Step-by-step explanation:
1..(abc-4)(abc-2)
we have to solve this problem using
(x+a)(x+b)=x^2+x(a+b)+ab.
where x=abc,a=-4 and b=-2.
(abc-4)(abc-2)=(abc)^2+abc(-4-(+2))+(-4×-2)
=a^2×b^2×c^2+abc(-4-2)+(+8)
=a^2×b^2×c^2-6abc+8✓
2. (4a^2+7)(4a^2+5)
we have to solve this problem using
(x+a)(x+b)=x^2+x(a+b)+ab.
where x=4a^2,a=7 and b=5.
(4a^2)^2 + 4a^2(7+5) +(7×5)
16a^4 + 4a^2(12) + 35
16a^2 + 48a^2 +
1..(abc-4)(abc-2)
we have to solve this problem using
(x+a)(x+b)=x^2+x(a+b)+ab.
where x=abc,a=-4 and b=-2.
(abc-4)(abc-2)=(abc)^2+abc(-4-(+2))+(-4×-2)
=a^2×b^2×c^2+abc(-4-2)+(+8)
=a^2×b^2×c^2-6abc+8✓
2. (4a^2+7)(4a^2+5)
we have to solve this problem using
(x+a)(x+b)=x^2+x(a+b)+ab.
where x=4a^2,a=7 and b=5.
(4a^2)^2 + 4a^2(7+5) +(7×5)
16a^4 + 4a^2(12) + 35
16a^2 + 48a^2 + 35✓